2005
DOI: 10.1007/11555261_51
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operational Mechanisms on Creativity in Design

Abstract: Abstract.Creativity is frequently referred to as an important dynamic of design. However, over 50 years of empirical research has suggested that social influences have a detrimental effect on creativity in collaborating groups. The results of this research indicate that design teams may not be as creative as they could be, resulting in a negative impact on the design process. In this paper we build upon previous research to identify what effect operational mechanisms have on creativity, in order to determine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, the effect of a number of approaches for development of creativity in schools is significant as the majority of the effect sizes are large. Finally, at the university level, five studies (Al-Ali Khaled, 2011;Eyadat & Eyaat, 2010;Hokanson, 2006;Seechaliao et al, 2011;Warr & O'Neill, 2005) showed large effect sizes of between 0.98 and 3.44. The other three studies (Cropley & Cropley, 2000;Hernandez et al, 2012;Park-Gates, 2001) presented medium effect sizes of between 0.32 and 0.65.…”
Section: The Effects Of Creativity Approaches Across Educational Levelsmentioning
confidence: 98%
“…However, the effect of a number of approaches for development of creativity in schools is significant as the majority of the effect sizes are large. Finally, at the university level, five studies (Al-Ali Khaled, 2011;Eyadat & Eyaat, 2010;Hokanson, 2006;Seechaliao et al, 2011;Warr & O'Neill, 2005) showed large effect sizes of between 0.98 and 3.44. The other three studies (Cropley & Cropley, 2000;Hernandez et al, 2012;Park-Gates, 2001) presented medium effect sizes of between 0.32 and 0.65.…”
Section: The Effects Of Creativity Approaches Across Educational Levelsmentioning
confidence: 98%
“…Rotter et al [30] argue that the expression of an idea in a real group causes all the members to think along the same lines, leading to duplication of ideas. However, the empirical evidence from our research [36] showed that real groups produce less duplication of ideas, suggesting that participants' awareness of ideas generated by other participants inhibited duplication. Each participant brings a different set of knowledge and background to a design activity.…”
Section: Experimental Overviewmentioning
confidence: 57%
“…de Bono's [8] emphasis on 'lateral thinking' and Lawson's [21] closely related discussion of designers as 'divergent thinkers' suggest that the more lateral or divergent the thinking of a group, the more creative the group may be considered. An analysis of the effect on divergent thinking caused by varying group composition will provide a deeper understanding of creativity in design, complementing our previous research [36] and informing how better to support creativity in design teams.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations